Double‐Gyroid Nanostructure Formation by Aggregation‐Induced Atropisomerization and Co‐Assembly of Ionic Liquid‐Crystalline Amphiphiles. (17th March 2020) - Uemura, Nanami; Kobayashi, Tsubasa; Yoshida, Shintaro; Li, Ya‐xin; Goossens, Karel; Zeng, Xiangbing; Watanabe, Go; Ichikawa, Takahiro
Abstract: We report a new molecular‐design principle for creating double‐gyroid nanostructured molecular assemblies based on atropisomerization. Ionic amphiphiles containing two imidazolium rings close to each other were designed and synthesized. NMR data revealed that the rotation of the imidazolium rings is restricted, with an activation energy as high as 63 kJ mol −1 in DMSO‐d6 solution (DFT prediction for a model compound in the vacuum: 90–100 kJ mol −1 ). Due to the restricted rotation, the amphiphiles feature "double" atropisomeric axes in their ionic segments and form three stable atropisomers: meso, R, and S . These isomers co‐organize into I a 3 ‾ d ‐type bicontinuous cubic liquid‐crystalline mesophases through nanosegregation of the ionic and non‐ionic parts. Considering the intrinsic characteristic of I a 3 ‾ d ‐type bicontinuous cubic structures that they are composed of intertwined right‐ and left‐handed single gyroids, we propose that the simultaneous presence of both R ‐ and S ‐atropisomers is an important contributor to the formation of double‐gyroid structures. Abstract : With both hands : A new molecular‐design principle for creating double‐gyroid nanostructured molecular assemblies based on atropisomerization is reported. Ionic amphiphiles with rotationally restricted imidazolium rings are used. Three stable atropisomers co‐organize into bicontinuous cubic liquid‐crystalline mesophases through nanosegregation of the ionic and non‐ionic parts.